STRATEGI INTERNALISASI NILAI-NILAI MORAL RELIGIUS DALAM PROSES PEMBELAJARAN DI PERGURUAN TINGGI - Mukhamad Murdiono (Jurnal Cakrawala Pendidikan, 2010)
Abstract: A Strategy to Internalize Moral and Religious Values in LearningProcesses in Higher Education. This study aims to describe a strategy tointernalize moral and religious values in learning processes in higher education.This research was a descriptive study employing the qualitative approach. Theresearch subjects were lecturers in the Department of Civic and Law Education,Faculty of Social Sciences and Economics, Yogyakarta State University. The datawere collected through interviews, observations, and documents. The datatrustworthiness was assessed by the triangulation technique. The results show thatstrategies to internalize moral and religious values in learning processes include:modeling, analyzing actual problems in society, developing contextual educativevalues, and strengthening moral values that the students have already possessed.Keywords: strategy to internalize moral and religious values, learning processes